Hubungan Dukungan Suami, Peran Bidan Dan Pengetahuan Ibu Terhadap Kejadian Baby Blues Pada Ibu Nifas Di BPM Bidan Lena Jakarta : Relationship Between Husband's Support, Midwife's Role and Mother's Knowledge of Baby Blues Occurrence in Post-partum Mothers at BPM Bidan Lena Jakarta - Anggraini, Dewi (Indonesian Scholar Journal of Nursing and Midwifery Science, 2024)
Introduction: Based on a preliminary study on secondary data at BPM Midwife Lena Jakarta in 2021 112 post-partum mothers gave birth at the BPM. From 112 post-partum mothers; based on secondary data from Lena's BPM in 2021, 15 post-partum mothers did not receive the support of their husbands, such as husbands never helping mothers with homework and husbands sometimes getting angry when the baby cries. Of the 112 post-partum mothers; 19 post-partum mothers felt anxious and worried that their babies would cry a lot and mothers felt that their sleep time was reduced. Of 112 post-partum mothers; 3 post-partum mothers felt uncomfortable with their current physical condition. Methods: This study aims to determine the relationship between the husband's support, the midwife's role, and the mother's knowledge of post-partum mother's baby blues. This type of research is Analytical and Descriptive with a cross-sectional approach. Results: there is a significant relationship between the husband's support and the incidence of baby blues in post-partum mothers with a p-value of 0,029 which is smaller than the alpha value of 0,029 <0,05. there is a significant relationship between the role of the midwife and the incidence of baby blues in post-partum mothers with a p-value of 0,030; the p-value is smaller than the alpha value 0,030 < 0,05. there is a significant relationship between mothers' knowledge of the incidence of baby blues in post-partum mothers with a p-value of 0,023; the p-value is smaller than the alpha value 0,023 < 0,05. Discussion: It is known that from a total of 37 respondents; the number of post-partum mothers who experienced symptoms of baby blues was 24 respondents (64,9%) which means that the variables of husband's support, the midwife's role, and a mother's knowledge played a big role in triggering the occurrence of baby blues in post-partum mothers.